Advanced thermoelectric energy recovery system in light duty and heavy duty vehicles: Analysis on technical and marketing challenges - Srinivasan, M.; Praslad, S.M. (IEEE, 2005)
Thermoelectric materials - materials that exploit a phenomenon in which the application of heat to combination of certain metals induces an electric current- are emerging as potentially important systems for increasing fuel efficiency and decreasing emissions in future automotive vehicles. The issue of thermoelectric efficiency for automotive application is examined from the standpoint of what material figures of merit (FOMs) enables solid-state devices to compete with conventional electricity generator or vapor compression refrigerators. It is estimated that FOMs of (ZT) equal to or greater than 8 is required. Some of the emerging new bulk materials may eventually reach that level of performance. The goal is to use that excess heat to create electricity that would support many of the existing vehicle system and to deliver the sufficient power to be able to replace mechanical system with electrical system. In this paper many of the automotive marketing issues and technical challenges are taken for discussion, like development of TE generator in light and heavy-duty vehicles, what type TE material, what are all the optimum design parameters like exhaust gas flow rate, its temperature, and suitable location in the vehicle are discussed. Apart from above, how the same TE material can be used in vehicular cooling/heating/climate control also discussed